Labor Supply under Participation and Hours Constraints: An Extended Structural Model for Policy Evaluations - Kai-Uwe Müller; Michael Neumann; Katharina Wrohlich (Institute of Labor Economics (IZA), 2018)
The paper extends a static discrete-choice labor supply model by adding participation and hours constraints. We identify restrictions by survey information on the eligibility and search activities of individuals as well as actual and desired hours. This provides for a more robust identification of preferences and constraints. Both, preferences and restrictions are allowed to vary by and are related through observed and unobserved characteristics. We distinguish various restrictions mechanisms: labor demand rationing, working hours norms varying across occupations, and insufficient public childcare on the supply side of the market. The effect of these mechanisms is simulated by relaxing different constraints at a time. We apply the empirical frame- work to evaluate an in-work benefit for low-paid parents in the German institutional context. The benefit is supposed to increase work incentives for secondary earners. Based on the structural model we are able to disentangle behavioral reactions into the pure incentive effect and the limiting impact of constraints at the intensive and extensive margin. We find that the in-work benefit for parents substantially increases working hours of mothers of young children, especially when they have a low education. Simulating the effects of restrictions shows their substantial impact on employment of mothers with young children.
Keywords: J22; J23; J16; J64; 330; labor supply; hours restrictions; involuntary unemployment; gender